Evidence for familial clustering in breast cancer age of onset. (28th November 2020) - Von Holle, Ann; O'Brien, Katie M; Sandler, Dale P; Weinberg, Clarice R
Abstract: Background: Familial clustering of age at onset would have implications for both personalized screening and aetiology, but has not been studied for breast cancer. Methods: We prospectively studied a cohort of 23 145 sisters to explore whether their breast cancer risk changed near the age at diagnosis of a previously affected older sister. Using an age-time-dependent variable in a Cox regression model, we estimated hazard ratios for breast cancer when participants were near their sister's diagnosis age, relative to similarly aged women whose sister was diagnosed at a very different age. To rule out a correlation driven by young-onset familial cancer, we separately investigated women who had enrolled at age 50 or older. Results: Of the 23 145 women, 1412 developed breast cancer during follow-up (median 9.5 years). The estimated hazard ratio was 1.80 (95% confidence interval: 1.18, 2.74) at their sister's age at diagnosis, suggesting a substantial increase in risk compared with women of the same age but whose sister was diagnosed at a very different age. Restriction to women who enrolled at or after age 50 produced similar results. Conclusions: This familial clustering suggests that there may be important genetic and/or early environmental risk factors that influence the timing of breast cancer, even when onset is late in life. Personalized screening might need to account for the age at which a sister was earlier diagnosed with breast cancer.